Moringa oleifera seeds powder as an alternative coagulant for beet sugar juice samples instead of lead acetate - Mohamed El-Kassem Hassouna; Mohamed Ezzat El-sharqawy; Mohamed Hassanien (Advances in Environmental Technology, 2020)
Lead acetate is the most common coagulant used in quality control laboratories in the sugar industry to clarify juice samples. Due to its known poisonous effects, health hazards, and extremely harmful impact on the environment, this study focused on finding an alternative coagulant that was efficient, safe, cost-effective, and eco-friendly. A powder made from Moringa oleifera (M.o) seeds, which is rich in phytochemicals with antimicrobials, was tested to produce a natural coagulant capable of clarifying the juice samples. The produced coagulant proved efficient and was potentially characterized by a better environmental performance than the extremely harmful lead acetate. An amount of three grams of M.o seedpowder proved to be an effective coagulant, achieving a 64.14 % removal of non-sugar compounds and led to the correct sugar polarimetric measurements. There is no way to compare the exorbitant price of lead acetate to the cost of naturally and available occurring Moringa seeds. The adsorption process was described by three adsorption isotherms, which were applied to evaluate the adsorption equilibrium.